A new set of qualitative reliability criteria to aid inferences on palaeomagnetic dipole moment variations through geological time - Biggin, Andrew J.; Paterson, Greig A. (Frontiers in Earth Science, 2014)
Records of reversal frequency support forcing of the geodynamo over geological timescales but obtaining these for earlier times (e.g., the Precambrian) is a major challenge. Changes in the measured virtual (axial) dipole moment of the Earth, averaged over several millions of years or longer, also have the potential to constrain core and mantle evolution through deep time. There have been a wealth of recent innovations in palaeointensity methods, but there is, as yet, no comprehensive means for assessing the reliability of new and existing dipole moment data. Here we present a new set of largely qualitative reliability criteria for palaeointensity results at the site mean level, which we term QPI in reference to the long-standing Q criteria used for assessing palaeomagnetic poles. These represent the first attempt to capture the range of biasing agents applicable to palaeointensity measurements and to recognize the various approaches employed to obviate them. A total of 8 criteria are proposed and applied to 312 dipole moment estimates recently incorporated into the PINT global database. The number of these criteria fulfilled by a single dipole moment estimate (the QPI value) varies between 1 and 6 in the examined dataset and has a median of 3. Success rates for each of the criteria are highly variable, but each criterion was met by at least a few results. The new criteria will be useful for future studies as a means of gauging the reliability of new and published dipole moment estimates.